ERROR ANALYSIS OF ENGLISH USED IN PUBLIC AREA IN PALANGKA RAYA - Sisilda, Rensi; Luardini, Maria Arina; Asi, Natalina (Journal Compound: Improving the Quality of English Education, 2021)
The research purpose is to analyze the problem of errors in the English language used in public area in Palangka Raya. This research method is a qualitative descriptive method. The source of data in this research is from photos of written English language that had taken by the researcher from advertising billboards, place names, commercial shop signs, and public signs on government buildings in public area in Palangka Raya. Based on the results of the research, it can be concluded that English language errors in the use of spelling and word choice are still found on public area in Palangka Raya. These English language errors can occur due to several factors. The factors that cause English language errors are the influence of the English language that was mastered first, inappropriate English language teaching, and the lack of understanding of English language users towards the language they use. In addition, weakness, lack of attention, and fatigue are also factors that cause language errors.